Social Educator ’ s Professional Competence Formation under Supervision Conceptual Model - Truskovska, Ženija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Nowadays prospective social educators must be able to commence their professional activity, quickly adapt to new and changeable circumstances, be able to use the acquired knowledge in practice, as well as educate and develop themselves in the context of lifelong education. The paper offers theoretically developed within the scientific research from 2008 to 2013 structural content and conceptual models forsocial educator's professional competence as a readiness for professional activity development under supervision.The research analysesthe problems of professional formation of the prospective social educators, studies the professional needs for educational support and opportunities to provide it under supervision within the study process in a higher education establishment. As a result of theoretical and personal experience definitions of professional competence and supervision for social educators are offered.